Cross-sectional study investigating the prevalence and causes of vision impairment in Northwest Portugal using capture-recapture - Ramos, Pedro Lima (2022)
Funding Information: This study was supported by FCT (COMPETE/QREN) grant reference PTDC/DPT-EPI/0412/2012 in the context of the Prevalence and Costs of Visual Impairment in Portugal: a hospital-based study (PCVIP-study). PLR is funded by FCT (COMPETE/QREN) grant reference SFRH/BD/119420/2016. AFM if funded by the faculty of Health and Life Sciences at Linnaeus University. Publisher Copyright: ©